The effects of intravesical therapy with hyaluronic acid for painful bladder syndrome: Preliminary Chinese experience and systematic review - Xiao-Min Han; Xin-Hua Wu; Bing Li; Feng Pan; Wen-Cheng Li; Shu-Lan Liu; Fu-Qing Zeng; Min Chen (Elsevier, 2015)
Objective: To present the preliminary results of treating a series of Chinese patients with painful bladder syndrome/interstitial cystitis (PBS/IC) using intravesical hyaluronic acid (HA). Materials and methods: A series of 13 patients with PBS/IC received first-line therapy followed by HA once-a-week for 4 weeks and then once monthly for 4 months. Outcomes measured included O'Leary-Sant Interstitial Cystitis Symptom Index (ICSI) and Interstitial Cystitis Problem Index (ISPI) scores, voiding frequency, and bladder capacity. Results: ISPI and ICSI scores were significantly (p < 0.001) decreased after treatment [median change (interquartile range): ISPI = 2 (2-3); ICSI = 3 (2-3)]. Voiding frequency and functional bladder capacity were significantly (p < 0.001) decreased [median change: 7 (6-8) times/d] and increased [median change: 190 (116-233) mL], respectively after treatment. Conclusion: Our case series supports the efficacy of intravesical HA in the treatment of PBS/IC.